Integrasi Teknologi Nano Sel Surya Dalam Pembelajaran IPA: Studi Kajan Pustaka - Nurmasyitah (Alpatih Harapan Semesta, 2025)
This research aims to examine the potential integration of nanotechnology, specifically solar cells, in the teaching of Natural Sciences (IPA) at the elementary and secondary education levels. Literature review shows that nanotechnology-based solar cells not only support the understanding of contextual renewable energy concepts but also contribute to strengthening students' critical and creative thinking skills. This integration enriches the science curriculum through a cutting-edge technology-based learning approach that is relevant to the challenges of the 21st century. The study results indicate that the use of nano technology can enhance science literacy, encourage a scientific attitude, and connect scientific concepts with real-life applications. This study also highlights the challenges of implementation and offers recommendations for developing a curriculum that is more responsive to technological advancements. These findings have important implications for educators and policymakers in designing nano-technology-based science learning innovations.